Role of oxidative stress and inflammatory markers in osteoporosis - Faheem Hadi; Tahir Maqbool; Tania Ahmed Shakoori; Tahir Muhammad; Sana Javaid Awan; Shabana Akhtar (International Journal of Applied and Experimental Biology)
Osteoporosis is a major health issue in post-menopausal females, however, it may occur before menopause. In middle aged women, osteoporosis directly relates to low bone mineral density (BMD) that consequently increases the risk of bone fracture. Several factors are involved in osteoporosis, however, the relationship of osteoporosis with oxidative stress and inflammatory response still needs to be investigated. In the current study, decreased values of different antioxidants displayed that they are necessary in maintaining bone homeostasis. A variety of all the oxidative stress parameters observed in this study, can be very effective to curing the disease.